Christian Education Major on Students' Mental Health - Adellia, Adellia; Pramana, Agung; Mantilie; Fernando, Ryan; Veronica, Maria (Indonesian Scientific Publication, 2023)
This study is based on an exploration of the narratives conveyed by students from Central Kalimantan related to mental health. Mental health here is more processed to their experience of getting a lot of daily tasks from each lecturer and panic in providing time, especially for students who work while studying. This research is based on qualitative research with data retrieval techniques through interviews. Results showed that there was the necessity of personal closeness between students outside of class hours to meet with the right appropriate behavioral counselor that suits the students' interests in the form of story sharing and reinforcement between parties to find capability space and the avoidance of boredom.